MATERNAL AND PERINATAL MORTALITY IN HELLP SYNDROME AT THE NATIONAL HOSPITAL CAYETANO HEREDIA - Román Pilco, Carlos (2015)
Objective: To determine the maternal and perinatal morbidity and mortality of pregnancies with HELLP syndrome at Cayetano Heredia National Hospital between July 1991 and December 1997. Material and methods: A descriptive study was made evaluating 20 HELLP syndrome pregnancies. RESULTS: A 3,7% incidence of the HELLP syndrome was found among patients with severe hypertension in pregnancy and/or eclampsia (533 cases). The major number of cases was found in the primigravidae group (60%), and in the group between 25 and 29 years old (35%), with a high percentage of preterm birth (70%) of newborns small for gestational age and a 30% low Apgar newborns. Among the HELLP syndrome 65% hadseizures and 6 patients (30%) died because of acute renal failure, cerebral damage and eclampsia. Conclusión: We found a high maternal and perinatal mortality in patients with HELLP syndrome.